WACANA REFORMASI DUNIA PENDIDIKAN DALAM PUISI “KENANGAN ANAKANAK SERAGAM” KARYA WIJI THUKUL - Nugraha, Alfian Setya (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2016)
Reformation is a term that refers to changes occurring in a system. Such changes may occur in the system of government, or the leadership system of a country or group. In Indonesia, the reformation refers to the college students’ movement that occurred in 1998, with the aim of overthrowing the power of the new order (orde baru). It continued to grow and expand to the education system in Indonesia so that the education system has changed. The situation is quite significant, due to the differences in viewpoints and educational purposes. Inequality among regions, human resources, and conditions of the society influence much on the education advancement in Indonesia. The author would like to describe the condition of education in Indonesia. The education system can be known through discourse in society. This can be determined by analyzing the poem by Wiji Thukul entitled “kenangan anak-anak seragam” by using AWK (Critical Discourse Analysis). The Discourse of Micheal Foucault and Roland Barthes’ semiotic were used by the authors as a knife in dismantling a reformation discourse of education existed in a poem. Keywords: Discourse, Reformation, Education